Shear Strengthening Behavior of Reinforced Concrete Beam Using Non-Stressing Strands - Kasyanto, Heri; Susanto, Ambar; Susilahadi; Enung (International Journal of Sustainable Construction Engineering and Technology, 2022)
Increasing the capacity of structures especially bridges can be done by various methods, one of them is by strengthening. Strengthening using strands has been used in various constructions. However, strengthening in reinforced concrete beams has not been done much because it will have many difficulties in the implementation. The focus of this research is shear strengthening using non-stressing strands. Strand is attached to the beam with epoxy. In certain intervals, strands are also anchored on the vertical side of the beam with U-shaped reinforcing steel. The basis of the research is experimental testing in the laboratory. The test specimens have consisted of a specimen without strengthening (BU-Normal) and 2 specimens with strengthening (BU-SV1 and BU-SV2). Dimensions of specimens are 250mm x 400mm x 1700 mm. In the laboratory, all specimens are loaded by a monotonic static load until collapse conditions. The results of the loading test at yield condition show that BU-SV1 and BU-SV2 can increase shear capacity respectively by 13.735% and 10.300% when compared to beams without strengthening (BU-Normal). Whereas at the collapse condition, BU-SV1 and BU-SV2 can increase shear capacities respectively by 34.886% and 25.360% when compared to beams without strengthening (BU-Normal).